Nutrition knowledge and healthy-eating attitudes: the role of physical activity and lifestyle factors in adults - Orhan, Bekir Erhan; Alkasasbeh, Walaa Jumah; Karaçam, Aydın; Canlı, Umut; Adıgüzel, Niyazi Sıdkı; Amawi, Adam Tawfiq (Frontiers in Nutrition, 2026)
BackgroundDiet quality and physical activity shape chronic-disease risk, yet the alignment between what adults know about nutrition and how they evaluate healthy eating remains unclear.MethodsAdults in Türkiye (N = 408; 46.3% women, 53.7% men; mean age 28.6 years) completed validated measures of nutrition knowledge (NKS) and attitudes toward healthy nutrition [ASHN; subscales: Information on Nutrition (IN), Emotion for Nutrition (EN), Positive Nutrition (PN), Malnutrition (MP)]. Lifestyle factors included smoking, alcohol use, and 7-day physical activity (sedentary/low/moderate/high). Analyses comprised t-tests, one-way ANOVA with Tukey tests, Pearson correlations, and multiple linear regression.ResultsKnowledge and attitudes were only weakly aligned: higher NKS related to lower ASHN Total (r = −0.18, p < 0.001) and to IN (r = −0.21), PN (r = −0.11), and MP (r = −0.17); EN was null (r = −0.01). In regression, IN (β = −0.17, p = 0.001) and MP (β = −0.16, p = 0.006) were independently associated with lower NKS; overall fit was small (R2 = 0.063; F(4,403) = 6.815, p < 0.001). Attitudes varied strongly by physical activity High > Low/Moderate/Sedentary for ASHN Total (F(3,404) = 10.10, η2 = 0.07), IN (F = 8.10), and PN (F = 11.11); EN showed no group difference. Smoking showed a paradox: knowledge was higher among heavier smokers (F(3,404) = 3.47, p = 0.010), whereas attitudes were less favorable (Never/Former > ≥ 11/day for ASHN Total; F = 6.47, η2 = 0.04). Non-drinkers reported higher ASHN than drinkers (t(406) = 2.48, p = 0.013) with lower MP (t(406) = 3.65, p < 0.001). Education displayed clear stepwise gradients for attitudes (e.g., ASHN Total F = 18.97, η2 = 0.12), but not for knowledge. Age correlated positively with ASHN Total (r = 0.27) and EN/PN/MP, but not with NKS (r = −0.07).ConclusionIn this adult sample, nutrition knowledge and healthy-eating attitudes were largely distinct. Attitudes especially belief- and practice-oriented facets tracked physical activity and other lifestyle factors, whereas knowledge did not. Interventions should pair education with motivation, self-regulation, and contextual supports to convert knowledge into healthier eating.